PHYSICAL ATTRIBUTE OF NEAT SEMEN AND OXIDATIVE STRESS PARAMETERS OF SEMINAL PLASMA OF JAFFARABADI BUFFALO BULLS - CHAVDA, B P; VALA, K B; SOLANKI, G B; SINGH, V K; PARMAR, K H (The Indian Journal of Animal Reproduction, 2021)
The present study was undertaken during summer season on four mature Jaffarabadi buffalo bulls at the CattleBreeding Farm, JAU, Junagadh, from March to June, 2021. A total of 24 semen ejaculates (6 ejaculates/bull) collectedby AV method were evaluated for physical characteristics and oxidative stress parameters, viz., lipid peroxidation(LPO/MDA) and GST enzyme activity in seminal plasma using standard procedures and assay kits on an autoanalyzer.The mean values of fresh semen characteristics observed were ejaculate volume 4.03±0.38 ml, spermconcentration 1464±82.05 x106/ml, mass motility score 3.79±0.08, individual motility 90.00±0.52%, live sperm92.04±0.59%, total sperm abnormalities 4.50±0.22%, intact acrosome 87.08±0.58%, and HOS reacted sperm83.00±0.49 %. Among all the parameters studied, only the sperm concentration and sperm morphological abnormalitiesvaried significantly (P
Keywords: Jaffarabadi bulls; Physical attributes; Oxidative markers; Semen; Seminal plasma